Is Age of Menarche Related with Body Mass Index? - Kazem Mohamad; Leila Jamshidi; Keramat Nouri Jelyani (Tehran University of Medical Sciences, 2013)
Prediction of the onset of menstruation (menarche age) using height, weight and Body Mass Index (BMI) is a major health procedure. The present study was conducted to determine the relationship between anthropometric indices and menarche age in 488 girls 11-17 years in southern Iran (Kish Island) in 2011.Data was collected using questionnaires as well as measurements of the children's height and weight. This data was analyzed using t-test and logistic regression.Median age of menarche of menstruated girls as inferred from the age of menarche cumulative distribution was 12.9 years. Mean (SD) BMI in menstruated and non-menstruated girls were 21.97 (4.5) and 19.17 (3.7), respectively. Mean (SD) weight and height of the menstruated girls were 53.65 (12.3) kg and 156.06 (5.5) cm, respectively which are higher than respective figures of the non-menstruated participants 43.70 (10.7) kg and 150.21 (6.3) cm, respectively. Our results revealed a significant correlation between BMI and menarche age.Menarche age and BMI are significantly correlated with higher BMI related to lower menarche age.